The Types and Functions of Prepositions in P.S. I Love You Movie by Richard Lagravenese - Wanodyatama, Nike Puspita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2020)
A research is entitled The Types and Functions of Prepositions in P.S. I Love You movie by Richard LaGravenese. This paper is intended to analyze the types of prepositions and the functions of prepositions. The writer uses descriptive method to establish this research. The aims of the research are to know the types of preposition and to identify the preposition functions which are used in P.S. I Love You movie. The result of the research shows the types of prepositions that appear in the movie are the preposition of time, preposition of place, preposition of manner, and preposition of direction. Meanwhile, the functions of prepositions that appear in P.S. I Love You movie are the function as head of prepositional phrases, noun phrase modifier, noun phrase complement, adjunct and adverbial, and the fuction as particle.Â Â